IMPROVING THE FORMATION OF EXPERIMENTAL SKILLS OF 9-CLASS CHEMISTRY STUDENTS (Scientific journal of the Fergana State University, 2023)
This article provides a brief overview of the history of the development of chemistry, its stages, the work carried out by ancient researchers and scientists in the field of chemical experiments, as well as the results of scientific research to improve the formation of experimental skills of students.